THE INFLUENCE OF THE CONSTRUCTION OF THE SITAKKURAK IRRIGATION DAM ON AREA DEVELOPMENT IN BARUS DISTRICT, CENTRAL TAPANULI DISTRICT - Bernardo Sondang H Lumban Gaol; Sirojuzilam; Riadil Akhir Lubis (RADJA PUBLIKA, 2024)
The Sitakkurak Irrigation Dam project which is being implemented in Barus District, Central Tapanuli Regency is a form of concern for the Central Government for the people. The irrigation project is carried out by the Ministry of Public Works, Directorate General of Water Resources. The objectives of this research are to: 1) Analyze differences in farmer production before and after the construction of the Akkurak irrigation weir, Barus District, Central Tapanuli Regency, and 2) Analyze what factors influence rice farmers' production in the Sitakkurak Irrigation area, Barus District, Central Tapanuli Regency. Research was carried out in Central Tapanuli Regency regarding the Influence of the Construction of the Sitakkurak Irrigation Dam on Regional Development in Barus District, Central Tapanuli Regency. The analytical method used in this research is the t-difference test and multiple regression analysis with a total of 69 respondents. The research results showed that there was a difference in farmers' rice production before and after the Sitakkurak irrigation dam and showed a significant influence because the results of the two paired sample tests were 0.000 < 0.05. The average value of farmers' rice production before the Sitakkurak irrigation dam was 3.77 tons per planting season and the average value of rice production after the Sitakkurak irrigation dam was 4.17 per planting season. These results show that there is a difference of 0.40 per planting season. Simultaneously, the factors of land area, rice seeds, fertilizer, pesticides and number of workers have a significant effect on rice production. Partially, the factors of land area, rice seeds, fertilizer and number of workers have a positive and significant effect on rice production, while the pesticide factor has a positive and insignificant effect on rice production.